2022
DOI: 10.3390/risks10020043
|View full text |Cite
|
Sign up to set email alerts
|

Bank Stock Return Reactions to the COVID-19 Pandemic: The Role of Investor Sentiment in MENA Countries

Abstract: In this study, we investigated the impact of COVID-19 investor sentiment (CS), number of cases (CC), and deaths (CD) on bank stock returns in 16 MENA countries. In addition, we examined the interaction effects of CS with CC and CD on bank stock returns. Lastly, we looked at whether Islamic banks outperformed conventional banks during the pandemic. Based on monthly data from the Middle East and North Africa (MENA) countries from February 2020 to July 2021, we used the clustered standard error fixed effect estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 83 publications
(103 reference statements)
1
11
0
Order By: Relevance
“…Investor sentiment was used as an independent variable, and the data came from Google Trends (GT) every week and from a year-over-year calculation. Albaity et al. (2022) also developed a GT index using a similar method to that described here.…”
Section: Sampling Methodology and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investor sentiment was used as an independent variable, and the data came from Google Trends (GT) every week and from a year-over-year calculation. Albaity et al. (2022) also developed a GT index using a similar method to that described here.…”
Section: Sampling Methodology and Variablesmentioning
confidence: 99%
“…Investor sentiment was used as an independent variable, and the data came from Google Trends (GT) every week and from a year-over-year calculation. Albaity et al (2022) also developed a GT index using a similar method to that described here. Google Trends (GT) is a tool that provides a normalised count of how many times a certain phrase or term was searched for on Google over a given period (Huang et al, 2020).…”
Section: Investor Sentiment (Ins)mentioning
confidence: 99%
“…The study found evidence of positive abnormal return during the lockdown period, confirming that the lockout has a favourable impact on stock market performance. Albaity et al (2022) found the impact of COVID-19-related cases, deaths and COVID sentiment on the stock return of the banking sector of 16 Middle Eastern and North African countries. The study found a negative impact of COVID cases and deaths, while pandemic sentiment did not have an effect.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 97%
“…Finding about the relationship between market sentiment and stock returns are mixed. [20] documented that investor sentiment does not influence stock returns. In the other side, [4] and [26] noted that during the pandemic, investor sentiment negatively affected stock returns since investors retracted their stock to avoid greater losses.…”
Section: Previous Researchmentioning
confidence: 99%
“…Numerous studies on the impact of investor attitude on stock returns have been conducted in various countries, including Indonesia ( [4,11,[20][21][22][23]). However, research that discusses the relationship of causality between the two variables is rarely carried out [24].…”
Section: Introductionmentioning
confidence: 99%